Virtual campus tours as strategic marketing communication: The role of personal innovativeness - Kurnadi Gularso; Henilia Yulita; Michael Christian; Sajjad Hussain (Rafandha Press, 2026)
Background: Virtual campus tours (VCTs) have emerged as an important digital marketing communication tool in higher education, enabling universities to engage prospective students through immersive and accessible virtual experiences. However, empirical evidence regarding the factors influencing prospective students’ intention to use VCTs remains limited. Purpose: This study examines the effects of Personal Innovativeness in Information Technology (PIIT), Perceived Ease of Use (PEOU), and Perceived Enjoyment (PE) on prospective students’ Behavioral Intention (BI) to use VCTs. Method: A quantitative study was conducted using an online survey involving 108 prospective undergraduate students in Greater Jakarta, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings: The results reveal that PIIT has a significant positive effect on PEOU. Furthermore, PEOU positively influences both PE and BI, while PE has a strong positive effect on BI. In addition, PE partially mediates the relationship between PEOU and BI. These findings suggest that designing VCTs that are both easy to use and enjoyable can effectively enhance prospective students’ intention to adopt virtual campus tours.